THE INFLUENCE OF SELF-ESTEEM AND INTERNET ADDICTION ON NOMOPHOBIA IN STUDENTS OF SMA NEGERI 1 KUALA - Desi Ritha Hutasoit; Rahmi Lubis; Suryani Hardjo (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
The current tendency of nomophobia is quite problematic for teenagers, especially students in this study. Nomophobia is certainly influenced by many factors. This study aims to analyze and see the influence of self-esteem and internet addiction with nomophobia. This study is included in quantitative research that is associative causal. The sample of this study was 275 students of SMA N 1 Kuala. The research data were collected using a research scale that was stated to be valid and reliable. The data analysis technique used multiple linear regression analysis. The results of the study showed that (1) There is a significant relationship between self-esteem and nomophobia. This can be seen in the model summary table where the correlation r is 0.422 and p = 0.000. The correlation is negative, meaning that if self-esteem is low, nomophobia also increases. The determinant coefficient R² is 0.178, meaning that 17.8% of nomophobia is influenced by self-esteem. Based on the results of this study, it can be stated that the proposed hypothesis 1 is accepted. (2) There is a significant relationship between internet addiction and nomophobia. This can be seen in the model summary table where the correlation r is 0.522 and p = 0.000. The correlation is negative, meaning that if internet addiction increases, nomophobia also increases. The determinant coefficient R² is 0.273, meaning that 27.3% of nomophobia is influenced by internet addiction. Based on the results of this study, it can be stated that the proposed hypothesis 2 is accepted. (3) Together, the variables of self-esteem and internet addiction have a significant relationship with nomophobia. This can be seen from the model summary table where the correlation r is 0.577 and p = 0.000. This means that together, variables X1 and X2 influence variable Y. Based on the results of this study, the three hypotheses proposed in this study are declared accepted. The determinant coefficient R² is 0.333, meaning that 33.3% of nomophobia is influenced by self-esteem and internet addiction. While 66.7% is influenced by other factors that cannot be explained in the regression equation (residual).